Avaliação citotóxica e genotóxica de Mimosa tenuiflora (Willd.) Poir. (Mimosaceae) - Silva, Viviane Araújo da (2012)
Mimosa tenuiflora (Willd.) Poir., popularly known as Jurema preta, is a plant family Mimosaceae, found mainly in the states of Piauí, Ceará, Rio Grande do Norte, Paraiba, Pernambuco, Alagoas, Sergipe and Bahia, which this species is typical of semi-arid areas of Brazil. In folk medicine, the bark of the stem is the main part of the plant used to treat various ailments such as burns and inflammations. This study aimed to investigate the cytotoxicity and genotoxicity of crude ethanolic extract (BSE) and Mimosa tenuiflora in prokaryotic and eukaryotic cells in order to encourage later, safely, its use as a source of potentially therapeutic drugs or act as pharmacological tools. To this end, we evaluated the antimicrobial activity against Gram negative and Gram positive clinical importance, investigated the potential cytotoxic utilizing the hemolytic activity and osmotic fragility (anti-hemolytic), as well as potential antioxidant and anti-oxidant in human erythrocytes, there was observed the potential mutagenic and anti-mutagenic in bacterial cells through the Ames test and also evaluated the clastogenic and aneugenic potential using the micronucleus test in peripheral blood of mice in vivo. The results showed that the EEB and the tannins of M.tenuiflora had antibacterial activity against all strains of Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli tested and this was characterized as strong with MIC ranging from 62,5 to 250 μg.mL-1. In the investigation of cytotoxic of M.tenuiflora it was observed that the extract did not induce a significant degree of hemolysis and even protected the erythrocyte membrane against hemolysis. In tests of the oxidizing activity of M.tenuiflora, this plant did not cause oxidation of hemoglobin and tests of the extract antioxidant activity behaved as a powerful antioxidant. In the investigation of genotoxicity, we observed that M.tenuiflora was not mutagenic, or in vitro tests and in vivo. Thus, the extract of M.tenuiflora has no cytotoxic or genotoxic that compromise its use as a source of potentially therapeutic drugs.